KAJIAN YURIDIS TERHADAP KASUS PENGHILANGAN PAKSA AKTIVIS TAHUN 1998 DARI PERSFEKTIF HUKUM PIDANA INTERNAIONAL - Shinta Agustina Iwan Kurniawan Siswa Elvandari (Masalah-Masalah Hukum, 2011)
Promoting for betere Human Rights Protection is one of the primary trigger factors that had led the reform movement in 1998. Unfortunately the movement itself must have been occured along with manyseriuously vioiating of human rights. One of them is the enforced disappearance of persons (activist) in 1997-1998 early in the beginning of reform movement. National Commission on Human Rights (Komnas HAM) has investigated the case in 2006 and found that there was a gross violation of human rights. The Commission submitted the report both to the legislative board and to the Attorney General Office. After a long process Legislative Board has recommended the government to establish an adhoc human rights court as stipulated in article 43, law number 26,2000 to try the case Kata kunci: Penghilangan PaksaAktivis, Hukum Pidana Internasional